A comparison of reactive oxygen species metabolism in the rat aorta and vena cava: focus on xanthine oxidase - Szasz, Theodora (American Physiological Society, 2008)
Reactive oxygen species (ROS) are important mediators in vascular biology. Venous function, although relevant to cardiovascular disease, is still understudied. We compared aspects of ROS metabolism between a major artery (the aorta) and a major vein (the vena cava, VC) of the rat, with the hypothesis that venous ROS metabolism would be overall increased compared with its arterial counterpart. Superoxide and hydrogen peroxide (H(2)O(2)) release in basal conditions was higher in VC compared with aorta. The antioxidant capacity for H(2)O(2) was also higher in VC than in aorta. Exogenous superoxide induced a higher contraction in VC compared with aorta. Protein expression of three major ROS metabolizing enzymes, xanthine oxidase (XO), CuZn-SOD, and catalase, was higher in VC compared with aorta. Because XO seemed a likely source of the higher VC ROS levels, we examined it further and found higher mRNA expression and activity of XO in VC compared with aorta. We also investigated the impact of XO inhibition by allopurinol on aorta and VC functional responses to norepinephrine, ANG II, ET-1, and ACh. Maximal ET-1-mediated contraction was decreased by allopurinol in VC but not in the aorta. Our results suggest that there are overall differences in ROS metabolism between aorta and VC, with the latter operating normally at a higher set point, releasing but also being able to handle, higher ROS levels. We propose XO to be an important source for these differences. The result of this particular comparison may be reflective of a general arteriovenous contrast.